Lecturers' assessment of impact of diamond radio on open distance education (ODE) programmes of University of Ibadan (2019)
The University of Ibadan, established as the pioneer higher educational institution by the colonial masters in 1948 has the responsibility of teaching, research and community service with Lecturers from inception employing different delivery modes in carrying out the mandates. Advancements in Information and Communication Technology (ICT) has led to a lot of developments occurring in teaching and learning which cannot be ignored; especially, the use of Radio broadcasting in facilitating teaching and learning activities in a conventional environment. The Distance Learning Centre (DLC) of the University was established in 1988 and in 2008, the Diamond Radio of the University was commissioned and immediately went into full operation. Just like many other Universities in Nigeria that operate campus radio, the Diamond Radio is not without clearly stated objectives part of which is the provision of teaching-learning interactive forum for relevant departments in the university and especially to enhance the Open Distance Learning programmes. Diamond Radio, which is a community radio has the responsibility of enhancing teaching by providing adequate platform for interaction between the open distance learning students and their respective lecturers, thereby enhancing the dual mode of open and distance education. This study investigates Lecturers’ Assessment of the impact of Diamond Radio on Open Distance Education of University of Ibadan. The study adopted ex-post facto research design of descriptive survey type. It involved two hundred (200) respondents including 58% males and 34% females, who were purposively drawn from the conventional and distance learning lecturers of the University of Ibadan. A structured questionnaire named "Diamond Radio Teaching Learning Activities Assessment Scale (DRTLAAS) was designed and validated at (r=0.98). Findings reveals that majority (70%) believed that that lectures are better delivered by University lecturers using Diamond Radio. Findings affirmed that Diamond Radio facilitates the provision for feedback mechanism especially from students after each lecture (63%>), further, Diamond Radio promotes interaction between lecturers and students in the University of Ibadan (89%). Findings also showed that Diamond Radio operates a standard platform for lecture delivery especially to Distance Learning Students of University of Ibadan (69%>). It was evident that Diamond Radio affords various Departments to participate in open air teaching (79%). Moreover, Students receive lectures regularly through Diamond Radio (66%), again information from the findings showed that students are incorporated into various activities of Diamond Radio (74%). It became clear that Diamond Radio has a standard training platform for students (70%). Findings helped understand that for students who desire to further advance in real world of work in mass communication, Diamond Radio is a good resource channel (67%). Operations of Diamond Radio show expected level of professionalism (72%) and Students are allowed to handle programmes in Diamond Radio (68%)